REFERENCE GENERATOR FOR VOLTAGE CONTROLLED POWER CONDITIONERS - Terrazas, T. M. [UNESP]; Marafao, F. P. [UNESP]; Monteiro, T. C.; Giaretta, A. R.; Matakas, L.; Komatsu, W.; IEEE (Ieee, 2011)
Voltage reference generation is an important issue on electronic power conditioners or voltage compensators connected to the electric grid. Several equipments, such as Dynamic Voltage Restorers (DVR), Uninterruptable Power Supplies (UPS) and Unified Power Quality Conditioners (UPQC) need a proper voltage reference to be able to compensate electric network disturbances. This work presents a new reference generator's algorithm, based on vector algebra and digital filtering techniques. It is particularly suited for the development of voltage compensators with energy storage, which would be able to mitigate steady state disturbances, such as waveform distortions and unbalances, and also transient disturbances, like voltage sags and swells. Simulation and experimental results are presented for the validation of the proposed algorithm.
Keywords: Phase-Locked-Loop; Dynamic Voltage Restorer; Uninterruptable Power Supply; UPQC; Positive Sequence